Development of Integrated Distribution and Inventory System Simulation Model Using Mobile Depot - Djanggu, Noveicalistus H (Faculty of Engineering, Universitas Tanjungpura, 2021)
Distribution activities are carried out to move an item from one point to another. Product distribution activities are conducted from the production area to the distribution or warehouse area, then from the warehouse to the retailer or consumer. Distribution activities can be established using various modes of land, river, ocean, and air transportation. Land transportation is greatly influenced by road conditions. River and sea transportation excels in carrying capacity which leads to the reduction of distribution costs. The disadvantages of water transportation are longer moving duration and dependence on weather. A warehouse is a typical facility used to accommodate inventory. Inventory system will generate holding costs. River transportation with a large carrying capacity can be used as a distribution medium and temporary warehouse. The land route in the West Kalimantan region is suitable for trucks with a moderate carrying capacity. River routes in West Kalimantan can reach several strategic areas, and river conditions have appropriate specifications for transportation mode with large capacities.Â The distribution and inventory system integration model using a mobile depot has been proposed in previous studies. Therefore, this research focuses on developing a simulation model for the aforementioned system. The results of this study are expected to provide information about the optimal value of the model configuration and strategy.